Evaluating Effects of Glatiramer Acetate Treatment on Amyloid Deposition and Tau Phosphorylation in the 3xTg Mouse Model of Alzheimer’s Disease - Dionisio-Santos, Dawling A.; Karaahmet, Berke; Belcher, Elizabeth K.; Owlett, Laura D.; Trojanczyk, Lee A.; Olschowka, John A.; O’Banion, M. Kerry (Frontiers in Neuroscience, 2021)
Neuroinflammation driven by the accumulation of amyloid b (Ab) can lead to neurofibrillary tangle formation in Alzheimer’s Disease (AD). To test the hypothesis that an anti-inflammatory immunomodulatory agent might have beneficial effects on amyloid and tau pathology, as well as microglial phenotype, we evaluated glatiramer acetate (GA), a multiple sclerosis drug thought to bias type 2 helper T (Th2) cell responses and alternatively activate myeloid cells. We administered weekly subcutaneous injections of GA or PBS to 15-month-old 3xTg AD mice, which develop both amyloid and tau pathology, for a period of eight weeks. We found that subcutaneous administration of GA improved behavioral performance in novel object recognition and decreased Ab plaque in the 3xTg AD mice. Changes in tau phosphorylation were mixed with specific changes in phosphoepitopes seen in immunohistochemistry but not observed in western blot. In addition, we found that there was a trend towards increased microglia complexity in 3xTg mice treated with GA, suggesting a shift towards homeostasis. These findings correlated with subtle changes in the microglial transcriptome, in which the most striking difference was the upregulation of Dcstamp. Lastly, we found no evidence of changes in proportions of helper T cell (Th) subtypes in the periphery. Overall, our study provides further evidence for the benefits of immunomodulatory therapies that alter the adaptive immune system with the goal of modifying microglia responses for the treatment of Alzheimer’s Disease.